Leading the 21st-century academic library : successful strategies for envisioning and realizing preferred futures - Eden, Bradford Lee (Creating the 21st-century academic library, 2015)
Leading the 21st Century Academic Library: Successful Strategies for Envisioning and Realizing Preferred Futures will explore the new roles and directions academic libraries are taking in the 21st century as a consequence of visionary leadership in exploring diverse futures.